Genetic analysis of the epidermal differentiation complex (EDC) on human chromosome 1q21: chromosomal orientation, new markers, and a 6-Mb YAC contig. - Marenholz, I; Volz, A; Ziegler, A; Davies, A; Ragoussis, I; Korge, B; Mischke, D (1996)
The epidermal differentiation complex (EDC) unites a remarkable number of structurally, functionally, and evolutionarily related genes that play an important role in terminal differentiation of the human epidermis. It is localized within 2.05 Mb of region q21 on human chromosome 1. We have identified and characterized 24 yeast artificial chromosome (YAC) clones by mapping individual EDC genes, sequence-tagged site (STS) markers (D1S305, D1S442, D1S498, D1S1664), and 10 new region-specific probes (D1S3619-D1S3628). Here we present a contig that covers about 6 Mb of 1q21 including the entire EDC. Fluorescence in situ hybridization on metaphase chromosomes with two YACs flanking the EDC determined its chromosomal orientation and established, in conjunction with physical mapping results, the following order of genes and STSs: 1cen-D1S442-D1S498-S100A10-THH-FLG- D1S1664-IVL-SPRR3-SPRR1-SPRR2-LOR- S100A9-S100A8-S100A7-S100A6-S100A5-S100 A4- S100A3-S100A2-S100A1-D1S305-1qtel. These integrated physical, cytogenetic, and genetic mapping data will be useful for linkage analyses of diseases associated with region 1q21 and for the identification of novel genes and regulatory elements in the EDC.